National income and expenditure on Aeducation - kathim saad alarajy (Iraqi Journal for Administrative Sciences, 2025)
Take the education sector occupies a large portion of the concerns of writers and researchers because of its important role in achieving the economic development process as it contributes to the provision of efficient human resources needed by the economic sectors as the lack of such cadres and development is a fundamental problem to the achievement of this process of economic development. Therefore, we find confirmation by economists according to their attitudes on the importance of the human race and considered the engine that pulls the economic development process forward. Has given so much of the world, with different degrees of economic development, a growing interest in the process of human capital formation and the need to increase spending by The research was based on the premise (that the low level of spending on education would be a major reason for the low level of scientific development, and access to staff is an efficient barrier to achieving the economic development process) The research aims to indicate the role of the education sector in the development process sought by the developing countries, including Iraq, in addition to its role in solving many economic problems such as unemployment and economic sectors, including the supply of needed skilled labor. And the statement of the relationship between increased spending on education and access to educational outputs capable of denominational leadership development in the country. The research concept and the concept of income and expenditure forms in addition to the reality of Iraq 's education system and its development in different educational levels, elementary, secondary and university in addition to the identification of indicators of expenditure on education and development. The research found a number of conclusions to mention some of them: Low rates of financial allocations to the education sector, which led to the low rate of compound growth of expenditure on education compared with the Arab countries and developing countries. High rate of growth in the number of students is greater than the growth rate of the number of universities, which impact on the scientific level of students and scientific competence of the outputs of education. The importance of spending on education in solving the problem of unemployment and cuts in rates.